2014
DOI: 10.1111/fare.12072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Couples Group to Enhance Father Involvement in Low‐Income Families Using a Benchmark Comparison

Abstract: Following an earlier randomized clinical trial, now with broadened sample criteria, 236 low‐income White, Mexican American, and African American couples participated in 16‐week Supporting Father Involvement couples groups, with assessments at baseline, 2‐, and 13‐months postintervention. Because couples in the earlier control condition experienced no benefits and some declines in adaptation, a control condition was not offered. Data from the original couples groups (n = 96) and controls (n = 98) served as benc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 21 publications
(28 reference statements)
2
49
0
Order By: Relevance
“…Father involvement, the first of two variables examined outside of the latent structural equation modeling, increased among immediate intervention participants according to reports of community mothers and CWS‐referred mothers and fathers. Previous studies in California (e.g., P. A. Cowan et al, , ), Canada (Kline Pruett et al, ), and the United Kingdom (Casey et al, ) also showed an increase in fathers' positive involvement with the children and their mothers. We noted that the amount of father involvement was unrelated to measures of father–child relationship quality and was therefore not included in our SEM model.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Father involvement, the first of two variables examined outside of the latent structural equation modeling, increased among immediate intervention participants according to reports of community mothers and CWS‐referred mothers and fathers. Previous studies in California (e.g., P. A. Cowan et al, , ), Canada (Kline Pruett et al, ), and the United Kingdom (Casey et al, ) also showed an increase in fathers' positive involvement with the children and their mothers. We noted that the amount of father involvement was unrelated to measures of father–child relationship quality and was therefore not included in our SEM model.…”
Section: Resultsmentioning
confidence: 83%
“…Supporting Father Involvement (SFI), a group intervention for fathers or for coparenting couples in primarily low‐income families, is an exception. Designed to (a) increase the quantity and quality of fathers' involvement with their children and (b) strengthen the relationship between fathers and their coparenting partners, SFI has demonstrated efficacy (P. A. Cowan, Cowan, Kline Pruett, Pruett, & Wong, ) and effectiveness (P. A. Cowan, Cowan, Kline Pruett, Pruett, & Gillette, ; Kline Pruett, Cowan, Cowan, & Pruett, ; Kline Pruett, Gillette, & Pruett, ) in terms of its impact on parents and on their children—an outcome rarely examined in studies of couple interventions.…”
mentioning
confidence: 99%
“…In terms of approaches to working with families, this finding emphasizes that programs that seek to encourage father involvement with children must attend to the nature and quality of the relationship between the two parents, not just the father’s parenting skills and attitudes (see, for example, the Supporting Father Involvement Project; Cowan et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Participants in the fathers‐only groups showed increased involvement in the care of their children but declining relationship satisfaction, whereas mothers and fathers who attended the groups as couples reported increases in father involvement, declines in parenting stress, and stable levels of both relationship satisfaction and child behaviors over 18 months. We went on to replicate these findings with a second, more ethnically diverse sample (P. A. Cowan et al, ), and a third trial in which half of the families were referred by child welfare staff because of earlier domestic violence, child abuse, or neglect (Pruett, Cowan, Cowan, Gillette, & Pruett, ). In this latter, higher‐risk sample, participation in a couples group intervention also produced statistically significant positive effects on reducing parents' relationship distress (conflict and violent problem‐solving 2 months after the groups ended).…”
Section: A Personal and Professional Perspective On Preventive Intervmentioning
confidence: 96%